Analytical and experimental studies on asymmetric bundle fiber displacement sensors - Lim, Kok Sing; Harun, Sulaiman Wadi; Yang, Hang Zhou; Dimyati, Kaharudin; Ahmad, Harith (Taylor & Francis, 2009)
A fiber-optic displacement sensor (FODS) is theoretically and experimentally studied using an asymmetrical bundled fiber. The bundled fiber consists of two parallel fibers with different core radial ratios (CRRs) to achieve different sensitivity and dynamic range for displacement measurements. Both analytical modeling and experimental observations show that the linear range and sensitivity can be adjusted by controlling the CRR between transmitting and receiving fibers. This increases the flexibility of the sensor, which can be used for precise non-contact sensing applications.